INTEGRATING READING AND WRITING SKILLS FOR TEACHING PARAGRAPH AND SHORT COMPOSITION WRITING A2 LEVEL LEARNERS - Yaqubjonova Ro‘zixon Mirkomil qizi; Mirolimova Rahnamo Davronbek qizi (Uz Conferences, 2025)
Integrating reading and writing skills is a valuable approach for teaching paragraph and short composition writing to A2 level learners. By connecting reading and writing activities, educators create a synergistic learning experience that enhances language acquisition, vocabulary development, and overall writing proficiency.